UPAYA MENINGKATKAN KREATIVITAS ANAK USIA 5-6 TAHUN MELALUI KOLASE BERBAHAN ALAM DI KELAS B TK NUR ADILAH SIMANGAMBAT - Sri Ulina; Rawalan Harapan Gaja; Isma Ayurani; Darliana Sormin; Jumaita Nopriani Lubis (Universitas Muhammadiyah Tapanuli Selatan, 2024)
Based on researchers' observations at Nur Adilah Simangambat Kindergarten, there were 10 children whose creativity had not yet developed with a percentage of 69%. To overcome this problem, researchers carried out research with the aim of increasing children's creativity through collage activities using natural materials. The type of research is Classroom Action Research (PTK) which consists of 2 cycles, per cycle 3 meetings with four stages, namely, planning, implementation, observation and reflection. The subjects in this study were 14 students in class B at Nur Adilah Kindergarten. In collecting data, researchers used observation, performance and documentation methods. This research is said to be successful if 11 children with a presentation of 80% are at the Developing According to Expectations stage. After the researcher carried out the research, the pre-cycle results showed that there were 0 children with a percentage of 0%, in cycle 1 there were 2 children with a percentage of 10%, in cycle 2 there were 12 children with a percentage of 84%, in accordance with the success target, so this research has been successful with The conclusion is that collage activities using natural materials can increase the creativity of children aged 5-6 years at Nur Adilah Simangambat Kindergarten.